IFN-? Production by Amyloid ?-Specific Th1 Cells Promotes Microglial Activation and Increases Plaque Burden in a Mouse Model of Alzheimer's Disease. - MILLS, KINGSTON; LYNCH, MARINA ANNETTA (My University, 2013)
Alzheimer?s disease (AD) is characterized by the presence of amyloid-b (Ab)?containing plaques, neurofibrillary tangles, and neuronal loss in the brain. Inflammatory changes, typified by activated microglia, particularly adjacent to Ab plaques, are also a characteristic of the disease, but it is unclear whether these contribute to the pathogenesis of AD or are a consequence of the progressive neurodegenerative processes. Furthermore, the factors that drive the inflammation and neurodegeneration remain poorly understood. CNS-infiltrating T cells play a pivotal role in the pathogenesis of multiple sclerosis, but their role in the progression of AD is still unclear. In this study, we examined the role of Ab-specific T cells on Ab accumulation in transgenic mice that overexpress amyloid precursor protein and presenilin 1 (APP/PS1). We found significant infiltration of T cells in the brains of APP/PS1 mice, and a proportion of these cells secreted IFN-g or IL-17. !b-specific CD4 T cells generated by immunization with Ab and a TLR agonist and polarized in vitro to Th1-, Th2-, or IL-17?producing CD4+ T cells, were adoptively transferred to APP/ PS1 mice at 6 to 7 mo of age. Assessment of animals 5 wk later revealed that Th1 cells, but not Th2 or IL-17?producing CD4+ T cells, increased microglial activation and Ab deposition and that these changes were associated with impaired cognitive function. The effects of Th1 cells were attenuated by treatment of the APP/PS1 mice with an anti?IFN-g Ab. Our study suggests that release of IFN-g from infiltrating Th1 cells significantly accelerates markers of diseases in an animal model of AD.
PUBLISHED
Keywords: Th1 cells; Th1 cells